Gabon : Request for a Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2020)
This paper highlights Gabon's Request for a Purchase Under the Rapid Financing Instrument (RFI). The coronavirus disease 2019 (COVID-19) pandemic and concurrent collapse in oil prices are expected to put the economy under extreme stress, particularly in a context of limited financial buffers. Economic activity will slow, and the fiscal and external positions will weaken, creating significant additional financing needs. In addition to immediate measures of containment, including border closures and curfews, the authorities are also taking significant steps to strengthen health policy responses and support households and firms. The RFI fund is expected to help create fiscal space for essential COVID19-related expenditure and catalyze donor support. The size and impact of the shocks is, however, subject to a considerable margin of uncertainty. The IMF continues to monitor Gabon's situation closely and stands ready to provide policy advice and further financial support if needed, in collaboration with other donors. The authorities should stand ready to suspend all emergency measures once the crisis subsides. Over the medium term, public debt needs to be put back on a firmly downward path. The decline in oil prices will necessitate faster fiscal adjustment and economic diversification.